IoT Platform Based Smart Parking Navigation System with Shortest Route and Anti-Collision - Kim, Dae Hyun; Park, Sung Hyun; Lee, Seungwoon; Roh, Byeong Hee (ISCIT 2018 - 18th International Symposium on Communication and Information Technology, 2018)
The number of automobiles that grow exponentially all over the world is causing serious problem of lack of parking space. There have been many studies to solve this parking space lack problem, but many of them have not been effective solutions to this problem because of cost and practical implementation problems. In this paper, we propose a smart parking platform with IoT and mobile applications. This platform consists of three systems. One system is the guidance of the shortest path parking place with Beacon and NFC Reader, the other system is the guidance of collision prevention between cars in the parking lot, and finally the parking information display and the parking reservation. To do our experiments, we constructed a mini-parking lot using three Beacon and 25 RFID, and assumed that the car is a smart phone. Because of the experiment, we have confirmed that these smart parking lot IoT platform systems are working.
Keywords: Anti collision; Beacon; Effective solution; Mobile applications; Parking informations; Parking reservations; Platform systems; Smart parking; Beacon; IoT; Smart Parking Lot Platform